Transmission Electron Microscopy to Follow Ultrastructural Modifications of Erythroblasts Upon ex vivo Human Erythropoiesis - Dussouchaud, Alice; Jacob, Julieta; Secq, Charles; Verbavatz, Jean-Marc; Moras, Martina; Larghero, Jérôme; Fader, Claudio M.; Ostuni, Mariano A.; Lefevre, Sophie D. (Frontiers in Physiology, 2022)
Throughout mammal erythroid differentiation erythroblasts undergo enucleation and organelle clearance becoming mature red blood cell. Organelles are cleared by autophagic pathways nonspecifically targeting organelles and cytosolic content or by specific mitophagy targeting mitochondria. Mitochondria functions are essential to coordinate metabolism reprogramming, cell death and differentiation balance, as well as synthesis of heme, the prosthetic group needed in hemoglobin assembly. In mammals, mitochondria subcellular localization and mitochondria interaction with other structures as endoplasmic reticulum and nucleus, might be of importance for the removal of the nucleus, i.e. the enucleation. Here, we aim to characterize by electron microscopy the changes in ultrastructure of cells over successive stages of human erythroblast differentiation. We focus on mitochondria to gain insights onto intracellular localization, ultrastructure and contact with other organelles. We found that mitochondria are progressively cleared with a significant switch between PolyE and OrthoE stages, acquiring a rounded shape and losing contact sites with both ER (MAM) and nucleus (NAM). We studied intracellular vesicle trafficking and found that endosomes and MVBs, known to be involved in iron traffic and heme synthesis, are increased during BasoE to PolyE transition; and autophagic structures like autophagosomes increase from ProE to OrthoE stages. Finally, consistent with metabolic switch, glycogen accumulation was observed in OrthoE stage.